Risk factors for acute kidney injury after initial acute aortic dissection and their effect on long-term mortality. Issue 1 (December 2016) - Kato, Akiko; Ito, Eri; Kamegai, Naoki; Mizutani, Minami; Shimogushi, Hiroya; Tanaka, Akihito; Shinjo, Hibiki; Otsuka, Yasuhiro; Inaguma, Daijo; Takeda, Asami
Abstract Background Several reports have discussed the risk factors for acute kidney injury (AKI) after thoracic aortic surgery and aortic dissection and the increased mortality in patients with AKI. However, there are few reports on the risk factors for AKI with combined medical and surgical treatment and the influence on mortality. The aim of this study was to clarify the risk factors and long-term effects of AKI on mortality and kidney function after acute aortic dissection in a cohort at our hospital. Methods We retrospectively investigated 96 patients with initial acute aortic dissection between April 2012 and January 2015. We divided the subjects into two groups: 65 with AKI and 31 without AKI using RIFLE criteria. The outcomes were all-cause mortality and the decrease in kidney function after 6 and 12 months. We extracted the risk factors for AKI by multivariate logistic regression using clinical parameters. Results A history of hypertension, type A aortic dissection, and low platelet levels were statistically significant factors to predict AKI after aortic dissection (odds ratio [OR] 9.1, 95 % confidence interval [CI] 1.42–58.5, p = 0.02; OR 25.2, 95 % CI 3.1–205.0, p = 0.003; OR 0.82, 95 % CI 0.68-0.98, p = 0.033, respectively). Three patients with AKI died and 1 patient recovered from AKI. The kidney function in survivors was similar in those with and without AKI. Although there were no significant differences in long-term kidney function between groups, long-term mortality was worse in the AKI group (p = 0.017). Conclusions Hypertension, type A aortic dissection, and low platelet levels were risk factors for AKI after aortic dissection, and AKI increased the 1-year all-cause mortality. A large-scale study is needed to verify our results.